Postseismic uplift of the Andes following the 2010 Maule earthquake: Implications for mantle rheology. Issue 4 (25th February 2017) - Li, Shaoyang; Moreno, Marcos; Bedford, Jonathan; Rosenau, Matthias; Heidbach, Oliver; Melnick, Daniel; Oncken, Onno
Abstract: Postseismic surface deformation associated with great subduction earthquakes is controlled by asthenosphere rheology, frictional properties of the fault, and structural complexity. Here by modeling GPS displacements in the 6 years following the 2010 Mw 8.8 Maule earthquake in Chile, we investigate the impact of heterogeneous viscosity distribution in the South American subcontinental asthenosphere on the 3‐D postseismic deformation pattern. The observed postseismic deformation is characterized by flexure of the South America plate with peak uplift in the Andean mountain range and subsidence in the hinterland. We find that, at the time scale of observation, over 2 orders of magnitude gradual increase in asthenosphere viscosity from the arc area toward the cratonic hinterland is needed to jointly explain horizontal and vertical displacements. Our findings present an efficient method to estimate spatial variations of viscosity, which clearly improves the fitting to the vertical signal of deformation. Lateral changes in asthenosphere viscosity can be correlated with the thermomechanical transition from weak subvolcanic arc mantle to strong subcratonic mantle, thus suggesting a stationary heterogeneous viscosity structure. However, we cannot rule out a transient viscosity structure (e.g., power law rheology) with the short time span of observation. Key Points: Uplift in the Andes and subsidence in the hinterland are observed in the 6 years following the 2010 Maule earthquake A geodetic data‐driven modeling strategy is used to infer a heterogeneous viscosity distribution in the subcontinental mantle Viscosity distribution correlates with the first‐order thermomechanical transition from volcanic arc to craton area